Changes and monitoring technology of human heart rate and blood oxygen saturation under high-altitude hypoxia - Liao, Yan; Lu, Dianxiang; Yang, Jin (Frontiers in Physiology, 2025)
High-altitude hypoxia affects human physiology and primarily regulates the cardiovascular system by hypoxia-inducible factor and relative factors. This review introduces physiological changes in heart rate and blood oxygen saturation, commonly used monitoring techniques, and their limitations for the diagnosis of acute mountain sickness (AMS). Under acute hypoxia, peripheral oxygen saturation (SpO2) decreases, and heart rate increases; under subacute hypoxia, SpO2 rebound but remain below sea level baseline values, and heart rate gradually decreases; under long-term hypoxia heart rate returns to baseline values at sea level, but SpO2 remains below them. Tibetans exhibit lower heart rate than Han Chinese at identical altitudes, while Andeans show elevated heart rate versus lowlanders. SpO2 reductions persist in Tibetans/Andeans but approach lowlander levels in Ethiopians. Cerebral oxygen saturation is also used as a complementary indicator of blood oxygen saturation and could be applied to the monitoring of high-altitude hypoxic level, but there are fewer studies in this area. Current heart rate and blood oxygen saturation monitoring mainly relies on photoplethysmography (PPG). Researchers are aiming to use more objective monitoring of PPG to diagnose AMS, mainly focused on heart rate and blood oxygen saturation. While they have been identified as potential early warning indicators of AMS, significant individual variability leads to use them as definitive criteria for AMS diagnosis difficultly. Future research requires enhanced monitoring precision, exploring how individual genetic differences impact hypoxic responses, and developing personalized prevention and treatment strategies in order to provide new insights into high-altitude medicine.